Recontextualizing Pesantren in International Scholarship: A Corpus-Based Semantic Profile Analysis - Ahmad Suhaili; Frans Sayogie; Muhammad Farkhan (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
Purpose Since the early 2000s, pesantren have been the most talked-about topic in international studies about Indonesian Islam. More and more Indonesian Islamic Higher Education Institutions are being published in academic journals around the world. This has made it easier for pesantren to be represented in Scopus-indexed journals, where these institutions are linked to a wide range of topics, from religious moderation to educational innovation. Since the term